1990
DOI: 10.1002/tera.1420410605
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine as a cause of congenital malformations of vascular origin: Experimental evidence in the rat

Abstract: Cocaine hydrochloride was administered to pregnant Sprague-Dawley rats as a single intraperitoneal dose or as two doses 1-4 hours apart. A single dose administered on day 16 of gestation was teratogenic in a dose-dependent manner, with 40 mg/kg being a no-effect dose and 50 mg/kg the lowest teratogenic dose; 80 mg/kg was lethal to the dam. Forty-eight hours after exposure to a teratogenic dose on day 16 of pregnancy, the fetuses showed severe hemorrhage and edema in the their extremities, particularly the foot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0
1

Year Published

1991
1991
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(55 citation statements)
references
References 15 publications
2
52
0
1
Order By: Relevance
“…Our findings of significant inhibition of PC-12 neuronal differentiation upon exposure to moderate to high cocaine levels suggest that cocaine may have direct effects on brain development, in addition to vascular side effects ( 16,17) that could contribute to the adverse neurodevelopmental outcomes. An alteration in neuronal differentiation could alter subsequent processes of synaptogenesis during the critical period of cell differentiation and rapid axonal and dendritic expansion.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Our findings of significant inhibition of PC-12 neuronal differentiation upon exposure to moderate to high cocaine levels suggest that cocaine may have direct effects on brain development, in addition to vascular side effects ( 16,17) that could contribute to the adverse neurodevelopmental outcomes. An alteration in neuronal differentiation could alter subsequent processes of synaptogenesis during the critical period of cell differentiation and rapid axonal and dendritic expansion.…”
Section: Discussionmentioning
confidence: 76%
“…Hypoxic ischemic insult secondary to systemic vascular side effects of cocaine could have contributed to these findings and have been reported in humans ( 1,17). Future animal studies must carefully control for vascular side effects, as in the Anderson-Brown study, to generate useful data on direct actions of cocaine in neural tissues.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Some studies report no increases in congenital abnormalities in rats or mice. 40 -42 Other studies in both species, however, have indicated that prenatal cocaine exposure may be teratogenic in a dose-dependent manner, resulting in abnormalities of the limbs, [43][44][45] cardiovascular, 43,46 genitourinary, 43,44,47,48 and central nervous systems. 43,44,46,47,49 Some human reports have likewise noted anomalies of the genitourinary 3,10,11,13,20,21 and cardiovascular systems, 1,8,14 -16 skull defects, 14 limb defects and intestinal atresias, 6,13,20,21,50 and a variety of central nervous system lesions 4,5,7,9,13,[51][52][53][54][55][56] in infants exposed to cocaine in utero.…”
Section: Discussionmentioning
confidence: 99%
“…This is the case of exome sequencing; however, it has successfully identified mutations in predominantly Mendelian phenotypes with high penetration alleles, whereas ABS may be caused by a combination of DNA variants, so it is necessary to perform a family-wide analysis and assess functional pathways that may be involved in ABS development to select the variants that should be validated by Sanger sequencing and, therefore, replicate the sequencing method in the family or the control population. 27,71 • Black population 73 • Unplanned or unintended pregnancy 16,27 • Smoking (> 15 cigarettes/day) 27,[70][71][72][73][74] • Exposure to cocaine 75,76 • Alcohol abuse 28 • High glycemic index in the diet 77 • Living in an attitudinal zone > 2000 meters above sea level 29,78 Obstetric factors • Nulliparity 15,21,26,71,73 • Multiparity…”
Section: Diagnosismentioning
confidence: 99%